MATHEMATICS AS A TOOL OF ACCOUNTING INSTRUCTION AND RESEARCH. - Zannetos, Zenon S. (The Accounting Review, 1963)
Abstract It is very difficult as well as unsatisfying to speak on the uses of mathematics in accounting for two main reasons. Firstly, because discussions of this nature convey the somewhat false impression that the only impetus toward changes, if any progress is evident in the use of mathematics in accounting instruction and research, has originated from without rather than from within the accounting profession, and that progress has been forced upon the accounting discipline by outsiders. Secondly, because the potential uses of mathematics in accounting are so many, within the time limitations of a meeting one can at best only survey the area. The author in this article did not attempt to explore fully the reasons accountants have not taken advantage of the existing body of mathematical knowledge earlier, but, according to him, he cannot help speculating briefly on this issue. It appears to him that the demands of management for new quantitative criteria of efficiency of operations and decisions both aggregative and partial, are presenting opportunities and pressures that accounting cannot ignore. Mathematical simulation, which has grown to maturity in the last few years, has had a pronounced influence on the design of feedback-control systems.